Application of 2, 5‐dihydroxyacetophenone with sublimation provides efficient ionization of lipid species by atmospheric pressure matrix‐assisted laser desorption/ionization imaging mass spectrometry. (27th June 2014) - Hayasaka, Takahiro; Goto‐Inoue, Naoko; Masaki, Noritaka; Ikegami, Koji; Setou, Mitsutoshi; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> Imaging mass spectrometry (IMS) is a powerful tool for detecting and visualizing biomolecules in tissue sections. Most IMS instruments are equipped with a high‐vacuum chamber for matrix‐assisted laser desorption/ionization (MALDI). However, the use of high‐vacuum conditions restricts the usage of the matrix to less‐volatile substances. We recently developed an atmospheric pressure MALDI instrument, named the 'mass microscope', to avoid this problem. The atmospheric pressure condition enables us to use volatile matrices. In this study, we compared the reliability of a volatile matrix, 2, 5‐dihydroxyacetophenone (DHAP) with that of a conventionally used matrix, 2, 5‐dihydroxybenzoic acid (DHB). Compared with the results obtained with DHB, the mass spectra obtained with DHAP showed a variety of signal species in a mass region corresponding to phospholipid species in both the positive and negative ion modes without any matrix‐derived signals. DHAP provided highly strong signals of ganglioside (GM1) species. We also compared two matrix deposition techniques for DHAP matrix: sublimation and spraying. We found that the sublimation method for applying DHAP matrix on a tissue surface can maintain ion images of lipid species, including ganglioside species only in a tissue. In contrast, the spraying method led the diffusion of GM1 species toward the outside of the tissue sections. Consequently, the sublimation method for applications of DHAP is adequate to analyze some types of lipid species including GM1 in atmospheric pressure MALDI IMS. Copyright © 2014 John Wiley & Sons, Ltd.